1986
DOI: 10.1093/clinchem/32.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of transferrin in human seminal plasma by a chemiluminescent method.

Abstract: We describe a luminescence immunoassay for measuring transferrin in human seminal plasma. Human transferrin conjugated with 7-[(N-4-aminobutyl)-N-ethylamino]naphthalene-1,2-dicarboxylic acid hydrazide was used to monitor the immunological reaction. The conjugate was stable for at least one year. The sensitivity (2 ng per tube) of the assay allows measurement of this protein in diluted seminal plasma. Results by this method (y) correlated well (r = .9681) with those by a conventional RIA method (x): y = 1.000x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The results we obtained for immunochemically reactive albumin in the semen of vasectomized men suggest that the testis is the principal source of seminal albumin, as previously demonstrated for transferrin (Orlando et al, 1985;Caldini et al, 1986). The decrease in seminal values of albumin in oligozoospermic and azoospermic patients was less marked than that found for transferrin, suggesting that the secretion of albumin is a process that is less sensitive to Sertoli cell impairment.…”
Section: Discussionsupporting
confidence: 76%
“…The results we obtained for immunochemically reactive albumin in the semen of vasectomized men suggest that the testis is the principal source of seminal albumin, as previously demonstrated for transferrin (Orlando et al, 1985;Caldini et al, 1986). The decrease in seminal values of albumin in oligozoospermic and azoospermic patients was less marked than that found for transferrin, suggesting that the secretion of albumin is a process that is less sensitive to Sertoli cell impairment.…”
Section: Discussionsupporting
confidence: 76%
“…Previous reports from this (Orlando et al, 1985, Caldini et al, 1986 and other laboratories (Holmes, Lipshultz & Smith, 1982) have demonstrated that, in man, 80% of seminal transferrin derives from the Sertoli cell. Moreover, seminal transferrin is below the normal range in patients with azoospermia resulting from severe seminiferous tubule damage without obstruction.…”
Section: Introductionmentioning
confidence: 56%
“…Moreover, seminal transferrin is below the normal range in patients with azoospermia resulting from severe seminiferous tubule damage without obstruction. In the same studies (Orlando et al, 1985, Caldini et al, 1986 a significant correlation was found between seminal transferrin levels and sperm number. Therefore, seminal transferrin may be a useful clinical index of seminiferous tubule function.…”
Section: Introductionmentioning
confidence: 63%